Pembuatan Sistem Informasi Pemesanan Toko Bunga Dan Buket (Florist) Berbasis Website - Nashalu Aprilianti; Rachmad Augy; Dwi Vernanda (Fakultas Ilmu Komputer, 2026)
Along with today's developments, especially generation Z who like to give gifts in the form of flower bouquets and so on, making the sale of flower bouquets experience significant development along with technological advances. To support this business, we design and build a website-based flower bouquet sales application. Users of this website-based application allow users to view the collection of bouquets and flowers available in the application, choose the collection of flower bouquets and the type of bouquet they want, and can make purchases online. Flower bouquets can also be customized to the customer's preferences and desires. The system development method used in designing or creating the web uses the agile deveploment method because the development process is carried out gradually and can adapt to changing user needs. The results of creating an information system are expected to be beneficial to owners, including managing customer data in an easier and more efficient way, data storage can save space, making it easier to search for data during data repair and recap, order status monitoring, and sales reports.